Zero stars, do not recommend eaudiobook - Wassmer, MJ (Recorded Books, 2024)
VACATION CHECKLIST Pack swim trunks. Apply sunscreen. Survive the apocalypse? Professional underachiever Dan Foster is finally taking a vacation. Sure, his life has been average at best, and yeah, he's never quite lived up to his potential. But after a few Miller Lites in paradise with his girlfriend, Mara, things are starting to look up. Then the sun explodes. With the island resort suddenly plunged into darkness (he really should've sprung for the travel insurance), Dan's holiday goes from bad to worse when elite guests stage a coup and commandeer supplies. As temperatures drop and class tensions rise, revolution begins to brew on the island, and Dan accidentally becomes a beacon of hope for the surviving vacationers. But when one six-person plane is discovered that could get them back to the mainland, Dan realizes he has a choice to make. Does he escape the island with Mara? Or does he stay and fight to become the most unlikely hero of the end of the world? "The end of the world has never been so fun! Explosively funny and terrifyingly plausible in its depiction of the apocalypse, this cinematic debut had me LOLing, cringing, and cheering throughout. I absolutely blazed through this earth-shattering action romp."—Josh Winning, author of The Shadow Glass